Pengaruh ROA, CR, DER dan TATO Terhadap Nilai Perusahaan (PBV) (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Pada Periode 2019-2021) - Sewa, Amelia; Wijaya Z, Rico; Ridwan, Muhammad (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to determine the influence of fundamental factors in the form of finansial ratios, return on asset (ROA), current ratio (CR), debt to equity ratio (DER) and total asset turnover (TATO) on price to book value (PBV) in manufacturing companies food and beverage sub-sector listed on teh Indonesian Stock Exchange in the 2019-2021 period. The sample used was 35 companies out of 63 companies that passed the criteria and were listed on the Indonesian Stock Exchange. The data used in this study are quantitative data sourced from secondary data in the form of financial reports of food and beverage sub-sector companies listed on the IDX in 2019-2021 through websites, namely www.idx.co.id, www.idnfinancials.com, www.indopremier.com and the official website of each company. The data analysis method used is descriptive statistics, multiple linear regression, classical assumption test and hypothesis testing. The analysis tool uses SPSS 26. The results of this study indicate that simultaneously, return on asset (ROA), current ratio (CR), debt to equity ratio (DER) and total asset turnover (TATO) have a significant effect on price to book value (PBV). Meanwhile partially, return on asset (ROA) influnces on price to book value (PBV). Current ratio (CR), debt to equity ratio (DER) and total asset turnover (TATO) do not have a significant effect on price to book value (PBV) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2019-2021.